Stakeholder participation in conservation of yellow-crested cockatoo (Cacatua sulphurea abbotti) and its habitat in Masakambing Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ihsannudin, Antriyandarti E. 2022. Stakeholder participation in conservation of yellow-crested cockatoo (Cacatua sulphurea abbotti) and its habitat in Masakambing Island, Indonesia. Biodiversitas 23: 3950-3959. The yellow-crested cockatoo (Cacatua sulphurea abbotti, Oberholser 1917) is found only on Masakambing Island, Indonesia. Its conservation efforts are now facing hardship due to massive exploitation of their habitat, and stakeholder contribution is essential. The study was conducted on Masakambing Island using a sequential exploratory mixed method design. The results show that based on a ladder of participation, central government, local government, and non-government organization (NGO) are at the second top of the ladder (co-learning), while the community group is at the lower level (cooperation) and the local community at the lowest (compliance ladder). Limited knowledge, resources, and group characteristics contribute to the failure to be at the top level. Meanwhile, the local government, NGO, and community groups achieve a large participation dimension. The central government reaches medium coverage, while the local community has the lowest coverage. Therefore, it is necessary to get support from all stakeholders and put the local community as the main actor using a pragmatic approach. The lack of consideration from the views of older people and community members may add to the complexity of defining financial exploitation, which can result in problems in detection, disclosure, and underreporting of incidences.
Keywords: Comunity, government, ladder, mixed-method, NGO